Weaning off heated humidified high flow nasal cannula successfully in a 24-week extreme low birth weight infant in South-South Nigeria: a case report - Enato, Izehiuwa G.; Uduebor, Joseph (International Journal of Contemporary Pediatrics, 2024)
The use of heated humidified high flow nasal cannula (HHHFNC) has become increasingly popular for providing noninvasive respiratory support for neonates with respiratory distress syndrome (RDS). However, there are several challenges to its use as primary respiratory support in extreme low birth weight (ELBW) preterm infants delivered before 28 weeks gestational age (GA), these include: lack of established guideline; and conflicting reports from studies on the risk of respiratory failure (apnea), necrotizing enterocolitis (NEC), bronchopulmonary dysplasia (BPD) and death. In Nigeria, HHHFNC is not widely known nor used in most neonatal care facilities, including level III Neonatal care facilities. Despite adequate literature search, there is little or no known report or guideline for the successful use of and weaning from HHHFNC in ELBW neonates, delivered before 28 weeks GA in the Country. We present the successful weaning from HHHFNC as primary respiratory support at 30 weeks post conception age (PCA) in an ELBW preterm infant (weighing 700 gm) with severe RDS, delivered at 24 weeks GA in a neonatal care facility in Nigeria. HHHFNC was commenced at 6l/min following surfactant administration and successfully weaned off at 2l/min at 30 weeks PCA, with no incidence of apnea, BPD, NEC, air leaks, nasal septum damage and death. HHHFNC used as noninvasive primary respiratory support for ELBW preterm neonates with severe RDS delivered before 28 weeks GA is effective and safe; in addition, weaning off HHHFNC in this group of infants at 30 weeks PCA should be explored and recommended as a guideline in Nigeria and globally.